Perusahaan dan strategi pemasaran - Putri, Rosyadah Rensy Dwi Murnisa (Maliki Interdisciplinary Journal, 2025)
A company is a business entity formed to generate profits through commercial or industrial activities. To achieve this goal, the company must be able to survive and thrive in the midst of increasingly fierce market competition. One of the key factors in maintaining the sustainability of the company is the implementation of an effective marketing strategy. Marketing strategy serves as an overall guide in directing marketing activities to achieve predetermined business goals. Marketing strategy includes identifying target markets, positioning products or services, managing the marketing mix (product, price, promotion, and distribution), and managing the marketing budget efficiently. With an integrated marketing strategy, companies can increase competitiveness, expand market share, and build strong relationships with customers. In addition, the right marketing strategy also plays a role in improving brand image and creating added value for the company. This study aims to examine the role of marketing strategy in supporting the success of the company, by reviewing related theories and previous findings. The results of this study are expected to provide a deeper understanding of the importance of planning and implementing effective marketing strategies in achieving company sustainability and growth.